Rare cases of appendicitis presented in KIMS Amalapuram, India: a clinical study - Kiran, M. Uday; Rakesh, B.; Rao, L. Hari Prasad; Avinash, P.; Manjusha, D. Amrita; K., Tejo Krishna; Raghuveer, M. V. B.; Pinnaka, Prasanth; Harika, D. Navya Sesha; P., Sundeep (International Surgery Journal, 2017)
RIF pain is a hall mark of acute appendicitis until proven otherwise decision making in a case of acute appendicitis may be difficult for junior surgeons hence we aimed at analysis in RIF pain. Out of 120 cases we found 3 rare entities they are PMP, CT of appendix and perforated appendix in LIF. Pseudomyxomaperinei and carcinoid tumour are rare presentations. Despite the current standard of treatment modalities as extensive surgical resection combined with chemotherapy, PMP and CT frequently recurs with treatment options being limited at recurrence and with severe impact on quality of life. Perforated appendix in LIF is also a rare presentation which needs appendicectomy, perforation closer with omental patch.